Clinical outcomes of arch expansion with Invisalign: a systematic review - Songyang Ma; Yunji Wang (BMC, 2023)
Abstract Objective This study aims to assess the scientific evidence regarding the clinical outcomes of Invisalign therapy in controlling orthodontic tooth movement. Materials and methods An electronic search was conducted on PubMed, Cochrane Library, Web of Science, Embase, and Scopus from November 2015 to November 2022 to identify relevant articles. Methodological shortcomings were highlighted, and an evaluation of the quality of the included studies was completed using the Risk of Bias in Non-randomized Studies of Interventions (ROBINS-I) tool. Results Fifteen non-randomized controlled trials were included in the analysis. Most non-randomized controlled trials (n=11; 73%) were rated with a moderate risk of bias according to the ROBINS-I tool. There were statistically significant differences between the pretreatment and posttreatment arches. The average expansion was significantly different from that predicted for each type of tooth in both the maxilla and mandible. Furthermore, the efficiency decreased from the anterior area to the posterior area in the upper arch. Conclusion Despite the fact that arch expansion with Invisalign® is not entirely predictable, clear aligner treatment is a viable option for addressing dentition crowding. The efficacy of expansion is greatest in the premolar area. More research focusing on treatment outcomes with different materials of aligners should be conducted in the future. Overcorrection should be considered when planning arch expansion with Invisalign. In the maxilla, the expansion rate decreases from the anterior to the posterior, and presetting sufficient buccal root torque of posterior teeth may result in improved efficiency of expansion.